2010
DOI: 10.1007/s11218-010-9146-7
|View full text |Cite
|
Sign up to set email alerts
|

Academic expectations as sources of stress in Asian students

Abstract: Education is highly valued in Confucian Heritage Culture (CHC) countries such as China, Taiwan, Singapore, Hong Kong, Japan and Korea but the expectations of parents, teachers and students themselves to excel academically can also be a source of intense stress for many students. The Academic Expectations Stress Inventory (AESI), developed by Ang and Huan (Educ Psychol Meas 66: 522-539, 2006) to measure parent, teacher and self expectations as sources of academic stress in Asian adolescents, was administered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
89
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(110 citation statements)
references
References 27 publications
9
89
0
6
Order By: Relevance
“…Findings of this study may help fill this gap and may be applicable to adolescent students in countries with similar educational and cultural experiences (e.g., China, Hong Kong, Japan, Singapore, and South Korea (Ang & Huan, 2006;Tan & Yates, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of this study may help fill this gap and may be applicable to adolescent students in countries with similar educational and cultural experiences (e.g., China, Hong Kong, Japan, Singapore, and South Korea (Ang & Huan, 2006;Tan & Yates, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Education is highly valued in countries such as China, Taiwan, Singapore, Hong Kong, Japan, and Korea because academic achievement is viewed as the main way of moving up along the social ladder in these societies (Ang & Huan, 2006;Tan & Yates, 2011). As mentioned previously, academic pressures constitute a main source of stress during adolescence.…”
Section: Outcomes Associated With Engagement Versus Disengagement Copingmentioning
confidence: 99%
“…Recent studies have shown that in Singapore society, which has a strong inclination towards the Confucian ideals of filial piety, obedience, loyalty, and collectivism, students develop school-related anxieties. In many ways, these anxieties are due to the expectations and pressures placed on them by parents, who consider children's school success as a matter of pride for the family and country (Anderson & Mayes, 2010;Ang & Huan, 2006;Ang et al, 2009;Lowe & Ang, 2012;Tan & Yates, 2011). Parents in Singapore have high academic expectations and are concerned about their child's achievements, beginning at the preschool age (Ebbeck & Gokhale, 2004;Sharpe, 2000, p. 123).…”
Section: Who and What Of Children In Singapore?mentioning
confidence: 99%